(untitled) (mathematica didactica, 2003)
Theoretical attempts and empirical studies on cognition and metacognition indicate that the attribution that only few pupils are able to solve complex problems or only few of them are to be enabled to do so is untenable. lf structures and strategies of mathematical thinking are analysed, it is achieved what hardly ever is considered to be manageable: Where mathematical thinking is allowed to set forth, this is where it can also be developed. The one who does not evade superior mathematical demands can deal with them - with the corresponding tools available. A proven tool for the dealing with complex demands is the formalization of knowledge.